NASOPHARYNGEAL MICROBIOTA IN CHILDREN WITH CHRONIC ADENOIDITIS - F S Ikramova; O.O Jaxonov (Antis Publisher, 2024)
Background: Adenoiditis is a common condition in children that can lead to significant respiratory complications and may affect overall health and quality of life. Specific Background: This study was conducted at the LOR-Department and polyclinic of the Bukhara Regional Children's Multidisciplinary Medical Center, along with the